Discussing ‘Inclusion’ in Shrinking Societies: The Case of Japan - Vanoverbeke, Dimitri; Kadomatsu, Narufumi (Zeitschrift für Japanisches Recht, 2018)
Conference organized by the KU Leuven and Kōbe University on 9 March 2017 in Leuven